2015
DOI: 10.1128/jvi.03478-14
|View full text |Cite
|
Sign up to set email alerts
|

Infection History Determines the Differentiation State of Human CD8 + T Cells

Abstract: After the resolution of the acute phase of infection, otherwise quiescent antigen-experienced CD8؉ T cells confer rapid protection upon reinfection with viral pathogens or, in the case of persistent viruses, help to maintain control of the infection. Depending on the type of virus, antigen-specific CD8 ؉ T cells have distinct traits, ranging from typical memory cell properties in the case of rapidly cleared viruses to immediate effector functions for persistent viruses. We here show that both the differentiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
99
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(108 citation statements)
references
References 52 publications
(85 reference statements)
4
99
0
5
Order By: Relevance
“…In contrast, the cytotoxic molecule granzyme K did not associate with Hobit (Figure 2D). This result is supported by previous reports showing that granzyme K, in contrast to Hobit, is not abundantly expressed in effector CD8 + T cells (20). To further investigate the characteristics of Hobit + T cells, we assessed the association of this transcription factor with key properties of cytotoxic T cells.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…In contrast, the cytotoxic molecule granzyme K did not associate with Hobit (Figure 2D). This result is supported by previous reports showing that granzyme K, in contrast to Hobit, is not abundantly expressed in effector CD8 + T cells (20). To further investigate the characteristics of Hobit + T cells, we assessed the association of this transcription factor with key properties of cytotoxic T cells.…”
Section: Resultssupporting
confidence: 91%
“…In contrast to the Hobit − fraction, the Hobit + CD4 + and CD8 + T cells lacked CCR7 expression (Figure 2F). These data suggest that Hobit + T cells do not respond to CCR7-dependent signals that instruct homing to lymphoid organs, in line with the observation that cytotoxic CD4 + and CD8 + T cells are absent from this compartment (20). …”
Section: Resultssupporting
confidence: 80%
“…Infection history has recently been shown to alter the proportion of EOMES and TBX21 producing cells in blood [40] including infection with the near ubiquitous Epstein-Barr virus (EBV). Given that EBV is necessary for MS [41] and abnormalities in both NK and CD8 memory cells are known to be associated with MS and poor clearance of EBV, we investigated if the ETlow phenotype predicted poor control of EBV using anti-EBNA-1 IgG levels as a marker of EBV control.…”
Section: Discussionmentioning
confidence: 99%
“…An additional pool of non-recirculating tissue-resident memory cells (Trm) has also been described (14). Despite certain phenotypic and functional overlap among these CD8 + T cell pools, this classification has been most useful to describe the level of differentiation that the CD8 + T cell compartment has endured under different inflammatory settings, such as autoimmunity, cancer, and acute and chronic viral responses (1517). Yet, perhaps the most significant achievement has been the identification of genes differently expressed by these pools, allowing to envision novel roles for CD8 + T cells (7, 1820).…”
Section: Cd8+ T Cell Differentiation: One-way Ticket To Pleiotropymentioning
confidence: 99%
“…Nowadays, alterations in CD8 + CD28 − T cells have been reported in almost every chronic inflammatory disease. Studies performed on CMV-seropositive elderly showed that a sizable fraction of CD8 + CD28 − T cells contains CMV-specific CD8 + T cells (17). The description in the elderly of an association between the accumulation of CD8 + CD28 − T cells, a phenomenon called memory CD8 + T cell inflation (36), CMV seropositivity, a decrease in survival rate and faulty in vivo humoral and cellular responses to vaccination, brought about the view that CD8 + Tem cells were terminally differentiated dysfunctional cells that contributed to immunosenescence and susceptibility to develop chronic inflammatory diseases (35–40).…”
Section: On the Origin Of Nk-like Cd8+ T Cells: Aging Viruses Cytokmentioning
confidence: 99%